PERSEPSI MAHASISWA MENGENAI KEWARGANEGARAAN DIGITAL DALAM PEMBELAJARAN ONLINE - Insani, Nisrina Nurul; Hamidah, Siti (Prosiding Temu Ilmiah Nasional Guru, 2023)
The rapid changes brought about by the disruption of digital technology have permeated the lives of citizens worldwide, bringing significant consequences that can have both positive and negative impacts. The negative effects become more pronounced when citizens are unable to keep up with these changes. Therefore, it is crucial for the state to prepare its citizens to face the challenges of digital technology disruption through digital citizenship education. This research aims to understand students' perceptions regarding the relationship between digital citizenship and online learning. The research method employed is a qualitative case study. Data is collected through interviews, surveys, document analysis, and observations to explore students' perceptions of how the principles of digital citizenship can be integrated into the design of online learning activities. Data analysis employs a thematic analysis approach to identify patterns and common themes. The research findings indicate that students' perceptions of digital citizenship principles, including responsible and ethical online behavior, can be successfully integrated into the design of online learning, with the potential to enhance student engagement and learning outcomes. This research provides valuable insights into how digital citizenship education can be enhanced in the context of online learning.